THE DEVELOPMENT OF CIRCULAR WIRE MAGNETIC INDUCTION EXPERIMENT DEVICE AS PHYSICS LEARNING MEDIA - Novia Ariyani; Hendar Sudrajat; Zulirfan Zulirfan; Rudi Sisyanto; Hernelis R (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2019)
In general, this research aims to produce a valid magnetic induction experimental device as a medium for learning physics in high school. The experimental device consists of experimental equipment and tool usage manual. In particular, this research aims to design, build, and validate devices for magnetic induction experiments on coiled wire as a physics learning media according to the research development steps. Three experts and two physics teachers as users have been involved to provide an assessment of the experimental devices that have been built. Assessment is carried out on the construction and content of the experimental device. The results of data analysis showed that every aspect of the assessment of the experimental tool was declared valid with a very good category (index validity 3.34) and the manual for using experimental tools was also declared valid with a very good category (index of validity 3.47). Thus, it can be said that the magnetic induction experimental device in circular wire is declared valid as a medium for physics learning.